Good governance in the health sector of Malawi: what lessons can be learnt from Malaysia? - Quddus, S. M. Abdul; Kaisi, Sheriff Abu Bakr (2015)
The level of inequity in health status and access to basic health care interventions remain high in Malawi (Zere, et al 2007). However, the people of Malawi want the health care service of the country to be efficient, effective and equitable (Kaisi, 2013). This paper examines the health care system and in particular how health care services are being delivered in Malawi with special reference to their connection with the issue of good governance. The paper is organized around the agenda of the health care sector of Malawi by focusing on the core concepts and parameters of “good governance” proposed by UNDP and adopted by Siddiqi et al, 2009). The field data of this paper were collected by using questionnaire and face-to-face interviews. The objectives of this paper are: a) to examine the system of service delivery in public hospital in Malawi; b) to explore the factors that promotes or prohibits good governance in public sector healthcare in Malawi; and c) to proffer possible solutions to existing challenges of quality health care service delivery in Malawi taking into consideration the health care service system in Malaysia.